Public Perception of Public Services at the Religious Affairs Office of South Dumai District - Ernita Puspa Dewi; Nadia Asiska (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
Marriage administration services are a form of public service that has important legal and social implications for the community. The Office of Religious Affairs (KUA), as a technical implementing unit of the Ministry of Religious Affairs, plays a strategic role in providing legal certainty regarding marital status. This study aims to analyze the quality of public services and public perceptions of marriage administration services at the Office of Religious Affairs in South Dumai District. This study used a qualitative approach with descriptive methods. Data were collected through observation, in-depth interviews, and documentation studies, with purposively selected informants consisting of KUA officers and community service users. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results show that the quality of public services at the KUA in South Dumai District is generally in the good category, particularly in the dimensions of responsiveness, reliability, and assurance. However, the tangible and empathy dimensions still require improvement, particularly related to limited infrastructure and individual attention to the community. This study confirms that the effectiveness of marriage administration services is determined not only by the performance of the apparatus, but also by the level of understanding and readiness of the community as service users. These findings provide important implications for improving the quality of public services through strengthening socialization, procedural transparency, and a more user-oriented service approach.